Makna Pengelolaan Lingkungan Pespektif Etik Profetik - Absori Absori; Khudzaifah Dimyati; Ridwan Ridwan (IAIN Ponorogo, 2017)
Abstract: Nowdays the disaster and anomaly of ecology are quite difficult to avoid. Concequently, nature has become a real threat to the survival of human. It occurs due to industrial activity, mining, transportation and agriculture as the mechine of capitalist ideology. The research employed the nomative-descriptive, and philosopy approach. This paper aims to (1) explore the spirit of theological and moral-ethical which are a bucker the capitalism or materialism ideology. (2) How is perspective and bid of moral-ethical of islam (prophetic) toward the meaning and management of the environment. The result shows that first, the desire for natural exploitation which is become a characteristic of capitalism or materialism ideology underpinned by a certain theological spirit that encourages domination and human exploitation on the nature. Moreover, the exploitation desire also underpinned by moral-ethical philosopy of hedonism or utilitarianism (pragmatism), which measures the highest kindness by accumulating the material as much as possible. Second, in the Islam perspective (prophetic), the nature interpreted as a something sacred, created by Allah, as one of the object for seeking knowledge of the greatest of Allah. And in the end it makes human closed to faithfulness (trancendence). In the prophetic ethical, the universum (nature) utilized for human prosperity. And it directed to humanization, liberation and trancendence in order to create a fair society and egalitarian. الملخص: ستكون الأضرار البيئية والشذوذ في المستقبل إنتشرت في هذا العالم، ولذلك أصبحت الطبيعة تهديدا حقيقيا لبقاء الحياة البشرية, وأسباب هذه المصيبة هي كثرة النشاط الصناعي، والتعدين، وعملية النقل، والزراعة التي تعتمد على روح وفلسفة رأسمالية. وبطريقة البحث الوصفي الديني وبالمدخل الفلسفي هدف هذا البحث إلى أولا: كشف الأرواح اللاهوتية والأخلاقية التي تقوم عليها الرأسمالية. ثانيا: ما رأي الإسلام والأخلاقية (النبوية) عن الإدارة البيئية ومعانيها. ونتائج هذا البحث أولا: رغبات الاستغلال الطبيعي التي تكون عادة وحجة لإيديولوجي الرأسمالية المادية، وبالإضافة إلى ذلك، فإن رغبة الاستغلال الطبيعي قد تكون معتمدة أيضا بفلسفة مذهب التحليلية المتعة والنفعية المادية التي تقيس الخيرات من خلال المواد الكثيرة العظيمة. ثانيا: وفي نظر الإسلام (النبوي) أن العالم هو شيء مقدس، الذي أنشأه الله للناس جميعا ليأخذه عبرة وتدبرا في عظمة الله، وأخيرا ليكون العالم وسيلة لتقريب الناس إلي الإيمان بالله. وفي رأي الأخلاق النبوية، أن العالم (الطبيعة) يستخدم لأجل الرحمة أو الرفاهية للناس جميعا, ليكون العالم يدور على طبيعته الإنسانية والتحررية والتجاوزية لتحقيق مجتمع عادل ومتكافيء.Abstrak: Dewasa ini bencana dan anomali ekologis semakin sulit terelakkan, akibatnya alam telah menjadi ancaman nyata bagi kelangsungan kehidupan umat manusia. Hal ini disebabkan oleh aktifitas industri, pertambangan, transportasi, dan pertanian sebagai mesin idiologi kapitalis. Dengan menggunakan metode normatif-deksriptif, dan pedekatan filosofis, tulisan ini bertujuan; pertama, mengungkap spirit teologis dan moral-etik yang menjadi penyokong ideologi kapitalisme/materialisme; kedua, bagaimanakah perspektif dan tawaran moral-etik Islam (profetik) terhadap makna dan pengelolaan lingkungan hidup. Dalam pembahasan dan analisis, tulisan ini menyimpulkan bahwa pertama, hasrat eksploitasi Alam yang menjadi karakteristik ideologi kapitalisme-materialisme, didukung oleh spirit teologis tertentu yang mendorng dominasi dan eksploitas manusia atas Alam. Selain itu, hasrat eksploitasi itu juga didukung oleh filsafat moral-etik hedonis-utilitarianisme (pragmatis), yang mengukur kebaikan tertinggi dengan mengakumulasi materi sebanyak mungkin. Kedua, dalam sudut pandang Islam (profetik), Alam dimaknai sebagai sesuatu yang sakral, diciptakan Allah, sebagai salah satu objek menggali ilmu-kebesaran Allah, dan pada akhirnya semakin mendekatkan diri manusia pada keimanan (transedensi). Dalam etik profetik, universum (Alam) di manfaatkan untuk kesejahteraan manusia, serta diarahkan dalam rangka untuk melakukan humanisasi, liberasi, transendensi, agar tercipta masyarakat adil dan egaliter.